Development and validation of an ensemble learning risk model for sepsis after abdominal surgery - Xin Shu; Yujie Li; Yiziting Zhu; Zhiyong Yang; Xiang Liu; Xiaoyan Hu; Chunyong Yang; Lei Zhao; Tao Zhu; Yuwen Chen; Bin Yi (Archives of Medical Science)
Introduction Although their importance has gained attention, the clinical applications of methods for screening patients at high risk of sepsis after abdominal surgery have been restricted. Therefore, we aimed to develop and validate models for screening patients at high risk of sepsis after abdominal surgery based on machine learning with routine variables.